Middle Class and Democracy: An Assessment on the 2014 Indonesian’s Presidential Election - Maxensius Tri Sambodo (Institute for Economic and Social Research, 2016)
This paper aims to assess the role of middle class in Indonesia’s democracy, with the particular focus of the last Indonesian Presidential election. This study uses econometric analyses to assess preferences of middle class in presidential election by exploring data at district/city and provincial. The main finding in this study strongly suggests that religious and personality are still important elements under the race of Indonesia president. This study also found that different group of middle class has different attitudes in selecting the presidential candidate and the upper group of middle class is more likely to select Joko Widodo. Finally, a fragile middle class and a relatively high number of abstainers could be a barrier toward more substantive democracy.AbstrakMakalah ini bertujuan untuk menganalisis peran kelompok kelas menengah dalam proses demokrasi di Indonesia, secara khusus peran mereka difokuskan pada hasil pemilihan presiden yang terakhir. Studi ini menggunakan pendekatan ekonometrik untuk mengalisis preferensi kelompok kelas menengah dalam memilih calon presiden, dengan melakukan eksplorasi data pada tingkat kabupaten/kota dan provinsi. Hasil studi menunjukkan, agama dan personalitas calon presiden menjadi faktor penting dalam pertarungan pemilihan presiden. Studi ini juga menunjukkan, berbagai kelompok dalam kelas menengah memiliki preferensi yang berbeda dalam memilih kandidat presiden dan kelompok kelas menengah atas cenderung memilih Joko Widodo. Akhirnya, kelas menengah yang rentan dan tingginya kelompok yang abstain, akan menjadi hambatan untuk menuju demokrasi yang lebih substantif.Kata kunci: Kelas Menengah; Demokrasi; Pemilihan Presiden; IndonesiaJEL classifications: A12; C33